A STUDY OF THE STABILITY OF RELATIVE INTERNAL EXPOSURE DOSE FOR INDIVIDALS AND FAMILIES IN RURAL SETTLEMENT - N. G. Vlasova; V. V. Stavrov; L. N. Eventova; A. V. Rozhko (Радиационная гигиена)
The analysis of internal exposure dose distribution of inhabitants of a settlement Kirov for 10-year period confirmed the hypothesis that each individual and also each family has its certain constant in time place at a dose distribution curve, i.e. the same percentile value of dose distribution corresponds to each of them. This regularity can be used as a basis of the methodological approach for reconstruction of individual exposure doses for any time period of the accident.